1975
DOI: 10.1002/aja.1001420308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gonadotropins on ovulation and ovarian histology in the immature mongolian gerbil

Abstract: The present study is an analysis of the effects of superovulatory doses of gonadotropins on the rate and time of ovulation and ovarian histology in immature gerbils. Groups were treated with various combinations of pregnant mare serum gonadotropin (PMSG) and human chorionic gonadotropin (HCG). The maximum superovulatory response followed treatment with 10 IU PMSG and 20 IU HCG. High dosages of PMSG inhibited superovulation, as did some combinations involving the highest dose of HCG. Entrapment of ova within co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…Conversely, the mean number of ova obtained in ovulated females was stable at around 30 when the interval between PMSG and hCG injections was 54 hours or more. This mean number of ovulated ova is comparable to the results of other investigators [1][2][3]. Mature female Mongolian gerbils have an estrus cycle of 4-6 days [7], a mean number of 3.9 pups (range 1-9) [8] and a mean number of ovulated ova of 6.6 [1] in their natural cycle.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Conversely, the mean number of ova obtained in ovulated females was stable at around 30 when the interval between PMSG and hCG injections was 54 hours or more. This mean number of ovulated ova is comparable to the results of other investigators [1][2][3]. Mature female Mongolian gerbils have an estrus cycle of 4-6 days [7], a mean number of 3.9 pups (range 1-9) [8] and a mean number of ovulated ova of 6.6 [1] in their natural cycle.…”
Section: Discussionsupporting
confidence: 77%
“…Ovulation, fertilization, and early cleavage in the Mongolian gerbil were investigated by Marston et al in the 1960s [1]. The protocol for inducing superovulation in the Mongolian gerbil has been examined by Mastron and Chang [1], Fisher and Fisher [2], and Ishijima et al [3]. Mastron and Chang [1] injected mature females with 10 to 40 IU PMSG (pregnant mare's serum gonadotropin) followed by 10 IU hCG (human chorionic gonadotropin) 52 hours later.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it seems that 8 IU PMSG is the best concentration among the different doses of PMSG that were studied in this research. Based on the study by Fischer and Fisher [ 40 ], the best superovulatory doses of PMSG on the rate and time of ovulation and ovarian histology in gerbils was observed with 10 IU PMSG. Based on the above consideration, we concluded that the optimal dose for superovulation and less alteration in uterine glycoconjugates of rats at implantation time was induced by the administration of 8-10 IU PMSG.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50 h later, 5 IU of hCG were injected intraperitoneally. The females were housed in the original cages for oocytes production or transferred into the male cages right after the hCG injection for mating (modified from (14)).…”
Section: Methodsmentioning
confidence: 99%